A role for Innexin2 and Innexin3 proteins from Spodoptera litura in apoptosis. - Tian Liu (Public Library of Science (PLoS), 2013)
Gap junctions formed by two hemichannels from two neighboring cells are cell-to-cell communication channels; hemichannels are communication channels between intracellular and extracellular environments. Hemichannels are hexameric proteins formed by connexins, pannexins, innexins and vinnexins. Innexin-hemichannels (innexons) exist in the lepidopteran cell surface, but their component innexins and functions have not been reported. Recent studies by others have demonstrated that hemichannels, connexons and pannexons from vertebrates serve as regulators of apoptosis via inactivating the PI3K/Akt signaling pathway. Here, the apoptogenic properties of innexons are demonstrated using two innexin cDNAs, Spli-inx2 and Spli-inx3, which were isolated from hemocytes of lepidopteran Spodoptera litura. Alignment analysis revealed that these two genes belong to a conserved innexin family, as they contain the insect signature YYQWV motif at the beginning of the second transmembrane domain. Immunofluorescence showed that two fusion proteins, Inx2-V5 and Inx3-V5, were localized predominantly in the cell membrane, cytoplasm and also nuclei. Ectopic expression in Sf9 cells and over-expression of Inx2 and Inx3 in Spli221 cells promoted apoptosis. In the Spli221 cells, apoptotic cells presented remarkable membrane blebbing. This study also showed that Sf9 and Spli221 cells undergo low level apoptosis under normal culture conditions, but not Hi5 cells. In Hi5 stable cell lines, biotinylation was used to isolate surface proteins and confirm Inx2 and Inx3 localization in the cell membrane and also further data showed that Hi5 cells may activate the PI3K signaling pathway via phosphorylating molecular Akt downstream. This result suggests that innexon-promoted apoptosis may be involving the PI3K/Akt signaling pathway. These findings will facilitate further examinations of the apoptotic regulation by the PI3K/Akt signaling pathway and comparative studies of innexons, connexons, pannexons, and vinnexons.